2019
DOI: 10.1177/1055665619835090
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Effects of Cheiloplasty on Maxillary Arch in UCLP Infants Using Three-Dimensional Digital Models

Abstract: Objective: To analyze and identify changes in the maxillary dental arch before and after cheiloplasty in a group of unilateral complete cleft lip and palate (UCLP) infants. Design: This is a cohort study. Material and Method: Study models from 16 infants with nonsyndromic UCLP, who were treated at Khon Kaen University, were taken before (T1) and after cheiloplasty (T2). The dental models underwent a process of scanning through a 3D scanner, from which 9 linear and 2 angular landmarks were evaluated. Paired t t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(49 citation statements)
references
References 33 publications
(48 reference statements)
4
41
0
3
Order By: Relevance
“…Other studies on unilateral cleft lip and palate agree with these results 2,3 . The literature suggest many factors for the changes in dental arch development in individuals with cleft lip and palate, such as: presence of cleft in secondary palate in individuals with BCLP, 24 cleft width, 25 and the iatrogenic effects of the rehabilitative surgeries 3,4 . Moreover, individuals with BCLP do not have the median palatal suture, whereas individuals with BCL do.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Other studies on unilateral cleft lip and palate agree with these results 2,3 . The literature suggest many factors for the changes in dental arch development in individuals with cleft lip and palate, such as: presence of cleft in secondary palate in individuals with BCLP, 24 cleft width, 25 and the iatrogenic effects of the rehabilitative surgeries 3,4 . Moreover, individuals with BCLP do not have the median palatal suture, whereas individuals with BCL do.…”
Section: Discussionmentioning
confidence: 56%
“…The following linear measurements were analysed: C–C′ (Intercanine distance)—transversal line between the eruption points of the primary canine; T–T′ (Intertuberosity distance)—transversal line between the left and right tuberosity; I–C′ (Left anterior intersegment length)—from the interincisive point to the eruption point of the left primary canine; I–C (Right anterior intersegment length)—from the interincisive point to the eruption point of the right primary canine; I–T′ (Left anteroposterior intersegment length)—from the interincisive point to the left tuberosity; I–T (Right anteroposterior intersegment length) from the interincisive point to the right tuberosity 1‐5,16,17 . The volume of the palatal bone shelves was analysed according to the methodology of the study of Pucciarelli et al, 2015, 18 whereas the area of the palatal bone shelves was evaluated according to Carrara et al, 2016 1 and Ambrosio et al, 2018 2 (Figure 1).…”
Section: Methodsmentioning
confidence: 99%
“…A drawback of this study is that measurements were performed using a slide caliper and the post-cheiloplasty dataset was seven months after surgery and thus included the effect of normal growth as well. In contrast, a study of Kongprasert et al (2019) , who used the same surgical technique at a median of 4 months, did not show an effect on the maxillary arch width, but found that the dental arch bended palatally.…”
Section: Introductionmentioning
confidence: 89%
“…Segundo Garrahy et al (2005) as dimensões reduzidas da maxila anterior indicaram que o efeito de distorção da cirurgia inicia precocemente e o pósoperatório imediato é crítico para a retrusão maxilar. Capelozza filho et al (1996( ), Li et al (2006 e Kongprasert et al (2019) sugeriram que a queiloplastia causa inibição do crescimento maxilar em indivíduos com fissura labiopalatina. A literatura mostra que outros fatores também podem afetar as dimensões dos arcos maxilares, tal como padrão genético facial (HONDA et al, 1995), gravidade da fissura (HONDA et al, 1995;CHEN, 2011), hipoplasia inerente à tecido palatino (HONDA et al, 1995;HONDA et al, 2002;MEAZZINI et al, 2011), a presença da fissura em si (SHAO; CHEN; YANG, 2014), habilidade do cirurgião (ROSS, 1987;SHAW et al, 1992; CARRARA, 2011) e diferenças nos protocolos de tratamento (DE LADEIRA; ALONSO, 2012).…”
Section: Variáveisunclassified
“…A análise dos modelos dentários por meio de pontos anatômicos préestabelecidos nas imagens tridimensionais tem sido usado na avaliação de indivíduos com fissura labiopalatina (MIKOYA et al, 2015, LIPPOLD et al, 2015RUSSEL et al, 2015;ZHU et al, 2016;CODARI et al, 2016, FALZONI et al, 2016SAKODA et al, 2017, AMBROSIO et al, 2018a, AMBROSIO et al, 2018bBRUGGINK et al, 2019;KONGPRASERT et al, 2019…”
Section: Introdução E Síntese Bibliográfica Introdução E Síntese Biblunclassified